2002
DOI: 10.1055/s-0037-1613241
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Fibrinolytic and Inflammatory Parameters in Human Adipose Tissue: Strong Contribution of TNFα Receptors to PAI-1 Levels

Abstract: SummaryPlasminogen activator inhibitor type 1 (PAI-1), a risk marker of atherosclerosis, is highly expressed in adipose tissue from obese subjects. PAI-1 is also considered as an acute phase protein. Recently, adipose tissue has been described as a source of inflammatory cytokines. Therefore, our aim was to study the relationships between PAI-1, and IL-6, TNF, TNF receptors (TNFRSF1s) and TGFβ1, in plasma and adipose tissue from obese (n = 60) and lean (n = 28) subjects. Study has been extended to plasminogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…57,58 Moreover, the invalidation of both TNF receptors decreased TGF-beta expression in the adipose tissue, 57 and in humans, TNF receptors, TGF-beta, and PAI-1 levels were strongly correlated within adipose tissue. 59,60 These results suggest that the TNF and TGF-beta pathways are connected within adipose tissue and may both control PAI-1 expression. The possible connection between insulin resistance, TGF-beta, and PAI-1 is further supported by the lowered expression of PAI-1 in FOXC2 ϩ/Ϫ mice in response to TGF-beta1 treatment 61 because FOXC2 has been implicated in insulin resistance.…”
Section: Arguments For the Contribution Of Tnf And Tgf-beta To Pai-1 mentioning
confidence: 81%
“…57,58 Moreover, the invalidation of both TNF receptors decreased TGF-beta expression in the adipose tissue, 57 and in humans, TNF receptors, TGF-beta, and PAI-1 levels were strongly correlated within adipose tissue. 59,60 These results suggest that the TNF and TGF-beta pathways are connected within adipose tissue and may both control PAI-1 expression. The possible connection between insulin resistance, TGF-beta, and PAI-1 is further supported by the lowered expression of PAI-1 in FOXC2 ϩ/Ϫ mice in response to TGF-beta1 treatment 61 because FOXC2 has been implicated in insulin resistance.…”
Section: Arguments For the Contribution Of Tnf And Tgf-beta To Pai-1 mentioning
confidence: 81%
“…In addition, the stromal cell fraction contained more PAI-1 mRNA than the adipocyte fraction. 32 However, in a study by Birgel et al 33 using an established in vitro model of human stromal cells undergoing in vitro adipose differentiation, it was demonstrated that there is a two-fold increase in the production of PAI-1 during the course of adipose differentiation at least under these experimental conditions. Again, the reason for this inconsistency is unclear.…”
Section: 24mentioning
confidence: 94%
“…PAI-1 can be produced in hepatocytes, 13 endothelial cells 18 and adipocytes. 10 Hepatic PAI-1 overproduction can cause systemic fibrinolytic system shutdown as shown by consequences of induction of the MET oncogene in mouse liver resulting in increased hepatic PAI-1 production and disseminated intravascular coagulation. 19 Binding of HGF to its specific receptor c-Met induces activation of intracellular tyrosine kinase domain of the c-Met and recruits a number of intracellular signaling molecules.…”
Section: Imagawa Et Almentioning
confidence: 99%
“…9 Adipose tissue may be an important source of PAI-1 with excess fat and subclinical inflammation. 10 However, fatty liver is common in metabolic syndrome, 11 and liver steatosis is strongly related to plasma PAI-1 levels, 12 suggesting that liver is an important source of increased circulating PAI-1. This study was designed to characterize molecular mechanisms influencing altered hepatic PAI-1 expression by HGF and to identify potential therapeutic approaches for attenuation of HGF-induced PAI-1 expression.…”
mentioning
confidence: 99%